ANALISIS ISI SILABUS, RPP, DAN BAHAN AJAR MATA PELAJARAN BAHASA MANDARIN SMP NUSA PUTERA, SMP KEBON DALEM, DAN SMP KARANGTURI SEMARANG (Universitas Negeri Semarang, 2018)
Abstract___________________________________________________________________The curriculum is one of the educational variables which have an important role in improving the education quality. Every educational unit has been given the freedom to arrange and develop its own curriculum which is based on the arrangement guideline developed by the National Education Standards(BSNP). Meanwhile, the government doesn’t provide the curriculum of Mandarin subject at junior high school level, so that the curriculum arrangement responsibility given to each educational unit. The purpose of this study is to determine the content and the curriculum development of Mandarin subject in the scope of syllabus and lesson plan at junior high school grade VII. The research approach which was used in this research is descriptive qualitative. Based on the findings in the form of Mandarin subject curriculum content analysis from SMP Nusa Putera, SMP Karangturi and SMP Kebon Dalem had been known that there are differences between the curriculum contents of each school. From the research findings, it is known that there is still weakness in the curriculum arrangement, both components and development. It is necessary to do further socialization for schools and the teachers in arranging the curriculum content in order to create a more effective and efficient curriculum. Abstrak__________________________________________________________________Kurikulum merupakan salah satu variabel pendidikan yang berperan penting dalam meningkatkan kualitas pendidikan. Setiap satuan pendidikan diberi keleluasaan untuk menyusun dan mengembangkan kurikulumnya sendiri yang berpedoman pada panduan penyusunan yang dikembangkan BSNP. Kurikulum bahasa Mandarin untuk tingkat SMP pemerintah tidak mengeluarkan sehingga penyusunannya diserahkan kepada masing-masing pihak satuan pendidikan. Tujuan penelitian ini adalah untuk mengetahui isi dan pengembangan kurikulum bahasa Mandarin dalam lingkup Silabus dan Rancangan Program Pembelajaran (RPP) SMP kelas VII. Pendekatan penelitian yang digunakan dalam penelitian ini adalah deskriptif kualitatif. Berdasarkan hasil penelitian yang berupa analisis terhadap isi kurikulum bahasa Mandarin dari SMP Nusa Putera, SMP Karangturi dan SMP Kebon Dalem diketahui bahwa terdapat perbedaan antara masing-masing isi kurikulum sekolah tersebut. Dari hasil penelitian masih terdapat kekurangan dalam penyusunan kuirikulum tersebut baik dari segi komponen maupun pengembangannya. Hal ini diperlukan sosialisasi lebih lanjut untuk pihak sekolah dan para pengajar dalam menyusun isi kurikulum agar dapat tercipta kurikulum yang lebih efektif dan efisien.